TRANSFORMASI PENDIDIKAN IPS DAN TANTANGAN MODERNITAS ABAD 21 DI ERA DISRUPSI DIGITAL TERHADAP GENERASI MILENIAL - Ixfina, Ficky Dewi; Fitriani, Siti Lailatul; Rohma, Siti Nur (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Research aims to investigate the transformation of Social Science Education (IPS) in facing digital disruption in the 21st century and its implications for the millennial generation. This study applies a qualitative descriptive method to understand the transformation of IPS education at MI Yatabu Surabaya in the era of digital disruption. The focus is on describing the challenges of modernity and the impact of digital disruption on the millennial generation. Involving interviews, observations, and document analysis, this research outlines the efforts of the madrasah in improving the quality of IPS education by utilizing technology. The results provide a deep insight into the learning strategies used, digital literacy enhancement, and the role of educators' human resources. In this context, madrasahs need to pay attention to innovative learning models, digital literacy, and the improvement of human resource quality as a response to the era of digital disruption. The implications of this research underscore the importance of adapting IPS education to the changing times